The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4739531
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic heterogeneity in the glass-like monoclinic phases of CBrnCl4−n, n = 0,1,2

Abstract: Glassy dynamics of rigid molecules is still a matter of controversy: the physics behind the relaxation process at time scales faster than that ruled by the viscosity, the so called Johari-Goldstein process, is not known. In this work we unravel the mechanism of such a process by using a simple molecular model in which the centers of mass of the molecules are forming an ordered lattice, and molecular reorientation is performed by jumps between equilibrium orientations. We have studied the dynamics of simple qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 76 publications
3
41
0
Order By: Relevance
“…The analysis of the isostructural CCl 4 shows that nonequivalent molecules in the unit cell perform reorientational jumps at different time scales due to their different crystalline environments. These results support the conclusion that the dynamic heterogeneity is intimately related to the secondary relaxation observed in these compounds 27,28,31 .…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The analysis of the isostructural CCl 4 shows that nonequivalent molecules in the unit cell perform reorientational jumps at different time scales due to their different crystalline environments. These results support the conclusion that the dynamic heterogeneity is intimately related to the secondary relaxation observed in these compounds 27,28,31 .…”
Section: Introductionsupporting
confidence: 88%
“…The dynamics of the monoclinic phases of CBr n Cl 4−n , n=0,1,2 compounds has been studied by means of dielectric spectroscopy and nuclear quadrupole resonance (NQR) spectroscopy 27,28 in the temperature range 100 -250 K and 80 -210 K, respectively. The former technique allows the measurement of the dynamic response within a broad time scale but it is insensitive to fine details of molecular motions, whereas the latter has a restricted time window but monitors the movement of individual chlorine atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these cases, it has been demonstrated that the main glass features show up, pointing out the relevance of the orientational degrees of freedom as far as the glass properties are considered. [20][21][22] Also, it should be stressed that for all those disordered systems the collective dynamics of the entities cannot be decoupled from the molecular or localized excitations, and thus the use of pertinent techniques, which encompass the different origins of disorder, should provide important highlights to the glass transition problem.…”
Section: Introductionmentioning
confidence: 99%
“…The presentation will describe the stable and metastable phases of those compounds revealed by the uncommon inclusion of the pressure variable as well as by the analyses of the two-component systems sharing them. Moreover, the emergence of unstable phases (glasses) [2] within the low-temperature domain will be analyzed and the similarities with the canonical glassformers will be discussed. …”
mentioning
confidence: 99%